Penyuluhan Pembuatan Gummy Candy Wortel dan Tomat sebagai Upaya Pencegahan Stunting pada Anggota Pengajian Langgar At-Taubah Kelurahan Bukuan Samarinda - Narsa, Angga Cipta; Bahar, Zulhaerana; Badawi, Satriani; Pamungkas, Barolym Tri; Irfan, Muhammad (Civiliza Publishing, 2024)
This activity aims to improve the knowledge and skills of mothers who are members of the Langgar At-Taubah study group, Bukuan Village, Samarinda, East Kalimantan regarding making gummy candy to prevent stunting in children. The method of implementing this service uses interactive counseling. The evaluation instruments for this service are pre-test and post-test. The results of this service show that the knowledge and skills of most mothers have increased, as evidenced by the presence of 76% of mothers in the post-test who managed to answer all questions correctly, previously in the pre-test only 45%.